Good to talk? : living and working in a communication culture - Cameron, Deborah, 1958- (Sage Publications, 2000)
"Good to Talk? is an attempt to look critically at what lies behind this upsurge of concern about talk in our workplaces, classrooms and private lives. It places these developments in historical context and relates their forms to the broader economic and social changes associated with globalization." "The book also poses questions about the social and political implications of talking about talking. Is 'communication' the key to solving the problems of modern life? Are the lessons in talking that are offered to us now the ones we most urgently need to learn? Is it time to challenge prevailing beliefs about what makes it good to talk?"--Jacket.